A Psycholinguistic Investigation of English Article Acquisition (Journal of Asian Development Studies, 2026)
348Journal of Asian Development Studies Volume15, Issue 1 (2026)A Psycholinguistic Investigation of English Article AcquisitionIshrat Aamer Qureshi1andMuhammad Yousaf2https://doi.org/10.62345/jads.2026.15.1.27AbstractThe area of English article acquisition remains underexplored. The use of an article requires the language user to understand the semantic context of article use. This research article aims to explore the rate of substitution and omission errors by Urdu L1ersin their L2use of English articles while writing compositions.Written compositions data was collected from (public and system) schools as well as from universities. Four age groups were included to ensure inclusion of both children and adults. Hence, there are four independent variables, viz., school type and learner’s age. The dependent variables include omission and substitution of the indefinite article ' a ’; omission and substitution of the definite article ‘the’. The errorsin article usewere identified, and SOC, TLU and UOC percentages were calculated. For post hoc analysis, a t-test was conducted to determine the extent to which the variation in article usage can be attributed to the independent variables in isolation and/or in combination. The results indicated that public school participants acquire definiteness before indefiniteness, whereas system school participants acquire indefiniteness before definiteness, as indicated by their SOC, TLU, and UOC error percentages. The study includes children and adults from two school types (representing different language inputs) and thus fills a gap in the current body of knowledge. In the current study, the significance of the independent variables, viz., system and age, is least significant in the age brackets 15-17 and 18-20. This may be attributed to insufficient language input during students' language classes. The study may be extended into a longitudinal study to examine the impact of language input and age over time.